Cochlear implantation outcome in straightforward cases: can we do more for adults who cannot understand speech using hearing aids alone?. (2nd December 2018) - Luntz, Michal; Khuri, Mahir; Khayr, Ranin; Gedaon Khuri, Wadeah; Yehudai, Noam; Shpak, Talma
Abstract: Background: Many adults with moderate–profound hearing loss whose speech recognition has deteriorated and are no longer benefitting from hearing aids (HAs) could benefit from cochlear implantation (CI). Of these, only <5% are implanted. In order to inform eligible patients about expected results and ease the route to implantation, better guidelines for candidate selection are needed. Objectives: To provide reliable guidelines by determining, in a well-characterized group of implantees, the minimal expected post-CI scores for monosyllabic (MS) word recognition. Patients and methods: In total, 20 adults unilateral implantees considered (prior to implantation) straightforward CI candidates were assessed ≥20 months post-CI. Their post-CI CI-aided thresholds and MS word recognition were compared to their pre-CI scores. In addition, SSQ12 scores were evaluated post-CI. Results: Post-CI, thresholds were 40 dB or better in all participants, and 35 dB or better in 95% of them. 90% scored 60% or better on MS words in quiet. In speech noise all scored 15–60% and 50% scored 45–60%. Poorer unaided pre-CI thresholds yielded greater patient satisfaction. Conclusions: Adults with moderate–profound hearing loss, whose speech recognition has deteriorated, are no longer benefitting from HAs and fulfil defined criteria for straightforward CI, should be referred for formal CI candidacy evaluation.